Enrichment of oral microbiota in early cystic precursors to invasive pancreatic cancer. Issue 12 (14th March 2019) - Gaiser, Rogier Aäron; Halimi, Asif; Alkharaan, Hassan; Lu, Liyan; Davanian, Haleh; Healy, Katie; Hugerth, Luisa W; Ateeb, Zeeshan; Valente, Roberto; Fernández Moro, Carlos; Del Chiaro, Marco; Sällberg Chen, Margaret
Abstract : Objectives: Intraductal papillary mucinous neoplasms (IPMNs) are pancreatic cysts that can progress to invasive pancreatic cancer. Associations between oncogenesis and oral microbiome alterations have been reported. This study aims to investigate a potential intracystic pancreatic microbiome in a pancreatic cystic neoplasm (PCN) surgery patient cohort. Design: Paired cyst fluid and plasma were collected at pancreatic surgery from patients with suspected PCN (n=105). Quantitative and qualitative assessment of bacterial DNA by qPCR, PacBio sequencing (n=35), and interleukin (IL)-1β quantification was performed. The data were correlated to diagnosis, lesion severity and clinical and laboratory profile, including proton-pump inhibitor (PPI) usage and history of invasive endoscopy procedures. Results: Intracystic bacterial 16S DNA copy number and IL-1β protein quantity were significantly higher in IPMN with high-grade dysplasia and IPMN with cancer compared with non-IPMN PCNs. Despite high interpersonal variation of intracystic microbiota composition, bacterial network and linear discriminant analysis effect size analyses demonstrated co-occurrence and enrichment of oral bacterial taxa including Fusobacterium nucleatum and Granulicatella adiacens in cyst fluid from IPMN with high-grade dysplasia. The elevated intracystic bacterial DNA is associated with, but not limited to, prior exposure to invasive endoscopic procedures, and is independent from use of PPI and antibiotics. Conclusions: Collectively, these findings warrant further investigation into the role of oral bacteria in cystic precursors to pancreatic cancer and have added values on the aetiopathology as well as the management of pancreatic cysts.